Prenatal arsenic exposure induces immunometabolic alteration and renal injury in rats - Singh, Radha Dutt; Tiwari, Ratnakar; Sharma, Vineeta; Khan, Hafizurrahman; Gangopadhyay, Siddhartha; Singh, Sukhveer; Koshta, Kavita; Shukla, Shagun; Arjaria, Nidhi; Mandrah, Kapil; Jagdale, Pankaj Ramji; Patnaik, Satyakam; et al. (Frontiers in Medicine, 2023)
Arsenic (As) exposure is progressively associated with chronic kidney disease, a leading public health concern worldwide. The adverse effect of As exposure on the kidneys of people living in As endemic areas have not been extensively studied. Furthermore, the impact of only prenatal exposure to As on the progression of chronic kidney disease also has not been fully characterized. In the present study, we examined the effect of prenatal exposure to low doses of As 0.04 and 0.4 mg/kg body weight (0.04 and 0.4 ppm, respectively) on the progression of chronic kidney disease (CKD) in male offspring using a Wistar rat model. Interestingly, only prenatal As exposure was sufficient to elevate the expression of profibrotic (TGF-β1) and proinflammatory (IL-1α, MIP-2α, RANTES, TNF-α) cytokines at 2 day, 12- and 38- week time points in the exposed progeny. Further, alteration in adipogenic factors (ghrelin, leptin and glucagon) was also observed in 12- and 38- week old male offspring prenatally exposed to As. An altered level of these factors coincides with impaired glucose metabolism and homeostasis accompanied by progressive kidney damage. We observed a significant increase in deposition of extracellular matrix components and glomerular and tubular damage in the kidneys of 38-weeks-old male offspring prenatally exposed to As. Further, overexpression of TGF-β1 in kidneys corresponds with hypermethylation of TGF-β1 gene-body, indicating a possible involvement of prenatal As exposure driven epigenetic modulations of TGF- β1 expression. Our study provides evidence that prenatal As exposure to males can adversely affect the immunometabolism of offspring that can promote kidney damage later in life.